Femtech and the Rise of Pervasive Medicine: Nightmare or Noble Dream? (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The rapid growth of the FEMtech market has raised social and bioethical concerns, particularly regarding mobile devices connected to women’s sexual and reproductive health. This article examines the bioethical implications of FEMtech and the kind of response this technology requires to address concerns about its reliability and safety, which are significant. In a context where patients’ personal data drives all healthcare activities, the emergence of a form of digital well-being that goes beyond traditional medicine raises new ethical questions and concerns. In the conclusion of the paper, FEMtech technologies are defined as a kind of «Middle-earth» between digital biotechnology and the natural ecology of women as potential mothers, highlighting how these technologies are the result of a neo-humanist practice generated by digital biocapitalism.
Keywords: Healthcare apps; habeas data; self-tracking; bio-surveillance; mHealth regulations